Uterine Malignant Mixed Mullerian Tumor (MMMT) - RASJIDI, IMAM; ANDRIANA, KUSUMA; MULIARTHA, IKG (Indonesian Journal of Cancer, 2010)
It was reported, a case of Uterine Malignant Mixed Mullerian Tumor (MMMT) in 54 years old woman who has not reached menopause with nulliparity. The patient was wrongfully diagnosed with cervical cancer earlier and on the second visit, diagnosed with geburt myoma and perform extirpation. Anatomic pathological result from extirpation was MMMT. The patient was then performed TAH-BSO, pelvic and periaortic limphadenectomy, and peritoneal washing cytology. After performing surgical pathological staging, this patient was diagnosed with uterine MMMT IC grade 3. Adjuvant chemotherapy of choice given was Doxorubicin-Etoposide-Platamin (DEP) for six series. However, drug eruption happened before the completion of the first series. It was decided, to replace DEP with paclitaxel for 5 series weekly.